MICROBIAL FUEL CELL (MFC) MENGGUNAKAN BAKTERI BACILLUS SUBTILIS DENGAN SUBSTRAT LIMBAH SEPTIC TANK SERTA PENGARUHNYA TERHADAP KUALITAS LIMBAH - Fitra Adi Prayogo; Agung Suprihadi; Budi Raharjo (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2017)
The power plant was still dependent on non-renewable energy is one factor in Indonesia fixed with the problems of electric energy crisis. Several lecturer have shown that B. subtilis can produced electricity through Microbial Fuel Cell (MFC). The purpose of this study is to measured the values of voltage, electric current, and power density as well as changes in the quality of waste water septic tank. Waste in a vacuum toilet can be of service